Pengaruh Responsiveness dan Empathy Terhadap Kepuasan Pasien Rawat Inap di Rumah Sakit Umum Hidayah Delitua - Fahrezy Try Cahya Putra Purwanto (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to determine and explain the effect of responsiveness and empathy on the satisfaction of inpatients at Hidayah Delitua General Hospital. The population in this study were inpatients at Hidayah Delitua General Hospital, with a sample size of 90 people. Data collection was conducted using questionnaires. The data analysis techniques used were multiple linear regression models and hypothesis testing using t-tests, f-tests, and determination coefficients, after the data had been tested using validity tests, reliability tests, and classical assumptions. Data processing was performed using SPSS. Based on the results of the hypothesis testing, it was found that: 1) Responsiveness has a positive and significant effect on patient satisfaction, 2) Empathy has a positive and significant effect on patient satisfaction. The Adjusted R Square analysis results indicate that Responsiveness and Empathy together influence patient satisfaction.